Penerapan Tenaga Surya sebagai Sumber Energi Alat Kupas dan Iris Bawang Merah di Ratu Jaya, Depok - Monika, Dezetty; Kusumaningyas, Ajeng Bening; Mulyadi, Wisnu Hendri (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
Setaman village that located in cipayung Depok have a home made product business fried onion. This home made product business do with the mother in this village . Each day this unit business can produced 10 kg of fried onion, wich is it can be last until 2-3 months. This home made product business is still carried out manually, starting from the onion peeling process to the onion frying process, so peeling and slicing 10 kg of onions takes 4 to 5 hours. Community Based Science and Technology Application Program (PPIBM) The Electrical Engineering Study Program will implement an automatic onion peeler and slicer sourced from solar panel with a capacity of 550 Wp. In this way, it can reduce the production time for fried onions, as proven by data showing that peeling 3 kg of onions takes 31 minutes and slicing 3 kg of onions only takes 14 minutes. Apart from that, with a solar panel installed with a capacity of 500 Wp with an average daily peak sun hours, 3 hours a day, the energy that can be produced is 1500 watthours. With 1500 watthours of energy, it can fulfill the energy needs of an onion peeler with a capacity of 350 watts for 3 hours. So it is hoped that the community can further increase the production of home made product business fried onion and can also create energy security in the community. Keywords: solar panel, energy, peeler onion, sliced onion